Data from: Decoding the anticancer activity of VO-clioquinol compound: the mechanism of action and cell death pathways in human osteosarcoma cells - León, Ignacio Esteban (2017)
Vanadium compounds were studied in recent years by considering them as a representative of a new class of non-platinum metal anticancer drugs. However, a few challenges still remain in the discovery of new molecular targets of these new metallodrugs. Studies on cell signaling pathways related to vanadium compounds have scarcely been reported and so far this information is highly critical for identifying novel targets that play a key role in the antitumor actions of vanadium complexes. This research deals with the alterations in the intracellular signaling pathways promoted by an oxovanadium(IV) complex with the clioquinol (5-chloro-7-iodo-8-quinolinol), VO(CQ)2, on a human osteosarcoma cell line (MG-63). Herein are reported, for the first time, the antitumor properties of VO(CQ)2 and the relative abundance of 224 proteins (which are involved in most of the common intracellular pathways) to identify novel targets of the studied complex. Besides, full-length human recombinant AKT1 kinase was produced by using an IVTT system to evaluate the variation of relative tyrosin-phosphorylation levels caused by this compound. The results of the differential protein expression levels reveal several up-regulated proteins such as CASP3, CASP6, CASP7, CASP10, CASP11, Bcl-x, DAPK and down-regulated ones, such as PKB/AKT, DIABLO, among others. Moreover, cell signaling pathways involved in several altered pathways related to the PKC and AP2 family have been identified in both treatments (2.5 and 10 μM) suggesting the crucial antitumoral role of VO(CQ)2. Finally, it has been demonstrated that this compound (10 μM, 6 h) triggers a decrease of 2-fold in in situ AKT1 expression.